Professional translation techniques to ensure accurate and genuine results in the target language - Salinas Martínez, Eleazar Eduardo; Hernández Gónzalez, José Remberto (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Disponible en soporte impreso